The current status of wind energy in Turkey and in the world - Ilkilic, Cumali; Aydin, Huseyin; Behcet, Rasim (Elsevier Sci Ltd, 2011)
The rapid increase in world energy demand, the depletion of conventional energy sources and the pollution caused by conventional fuels have increased the importance of developing new and renewable energy sources. Additionally, technological developments have resulted in increased energy demand for the entire world, including Turkey, especially for electrical energy. At present, wind energy is receiving considerable attention. This report focuses on the current status of wind energy in Turkey and in the world. An overview of wind energy in Turkey is presented, and its current status, application, support mechanisms and associated legislation in Turkey are described. Wind energy and its status in the world are also addressed. It can be concluded from this analysis that wind energy utilization in Turkey and throughout world has sharply increased. Turkey has an abundance of wind energy sources. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; Turkey; Electricity production